The Effect of Research-Based Learning Models Through The Photomath Application On The Mathematics Learning Outcomes Of 10th Grade Students - Grace Amelia Gultom; Rianita Simamora; Gayus Simarmata (Jurnal Ilmu Sosial dan Humaniora, 2025)
This study aims to determine the Effect of the Inquiry Learning Model Through the Photomath Application on the Mathematics Learning Outcomes of Class X Br. 2 Students of State Vocational School 1 Pematangsiantar Academic Year 2025/2026. The type of research used in this study is quantitative research. In this study, the design form used is One-Shot Case Study. This research will be carried out at State Vocational School 1 Pematangsiantar, which is located at Jl. Bali No. 5, Bantan, Kec. Siantar Bar., Pematang Siantar City, North Sumatra 21142. The research implementation time is planned to last for approximately 1 month in the odd semester of the 2025/2026 academic year. Based on the results of data analysis and discussion, it can be concluded that there is a positive and significant influence of the use of the inquiry learning model through the photomath application on the mathematics learning results of class X BR 2 students of SMPK Negeri 1 Pematangsiantar in the 2025/2026 academic year. The influence is shown through the regression equation Y = 10.639 + 0.069X, with a b value = 0.069. By means of the t-test, namely thitung > ttabel (2.109 > 2.048) that it is significant and by using the coefficient of determination it can be seen that the influence is 13.7